2014
DOI: 10.1016/j.yexcr.2013.12.025
|View full text |Cite
|
Sign up to set email alerts
|

miR-92a family and their target genes in tumorigenesis and metastasis

Abstract: The miR-92a family, including miR-25, miR-92a-1, miR-92a-2 and miR-363, arises from three different paralog clusters miR-17-92, miR-106a-363, and miR-106b-25 that are highly conservative in the process of evolution, and it was thought as a group of microRNAs (miRNAs) correlated with endothelial cells. Aberrant expression of miR-92a family was detected in multiple cancers, and the disturbance of miR-92a family was related with tumorigenesis and tumor development. In this review, the progress on the relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
78
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 59 publications
1
78
0
2
Order By: Relevance
“…In the past several years, more and more miRNAs have been confirmed as modulators of cell proliferation, apoptosis, and therapy resistance in lung cancer [14,15]. Among them, miR-92a attracts much attention because it can regulate tumor progression in a variety of cancers as an oncogenic or a tumorsuppressive miRNA [16][17][18][19][20][21]. Although, recently, a study has been demonstrated that miR-92a mediates STAT3-induced MMP activity and invasiveness by inhibiting RECK in lung cancer [22], the detail function especially in regard to response to chemotherapy and underlying molecular mechanism of miR-92a in NSCLC have not been totally elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In the past several years, more and more miRNAs have been confirmed as modulators of cell proliferation, apoptosis, and therapy resistance in lung cancer [14,15]. Among them, miR-92a attracts much attention because it can regulate tumor progression in a variety of cancers as an oncogenic or a tumorsuppressive miRNA [16][17][18][19][20][21]. Although, recently, a study has been demonstrated that miR-92a mediates STAT3-induced MMP activity and invasiveness by inhibiting RECK in lung cancer [22], the detail function especially in regard to response to chemotherapy and underlying molecular mechanism of miR-92a in NSCLC have not been totally elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…miR-486 -5p (75), miR-1266 (76) or miR-218 (77). Furthermore, we identified oncogenic factors among the down-regulated miRNAs, such as miR-25 and miR-92a (78) and the miRNA family miR-221/222, which is known to promote EMT (79).…”
Section: P53-mediated Regulationsmentioning
confidence: 99%
“…It has been suggested that miRNAs are predicted to regulate 30% of human genes (Carthew, 2006). Many studies have identified that miRNAs are potent drivers of various biological processes, including cell proliferation, cell differentiation, apoptosis and tumorigenesis (Zamore and Haley, 2005;Li et al, 2014;Tufekci et al, 2014). Recent emerging evidences have suggested that differential expression of miRNAs was related to various human cancers development and progression by regulating the expression of tumor suppressor genes or proto-oncogenes (Cui et al, 2014;Donadelli et al, 2014;Gu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%